2023
DOI: 10.1186/s40793-023-00526-5
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial community composition is more stable in kiwifruit orchards relative to phyllosphere communities over time

Ziva Louisson,
Louis Ranjard,
Hannah L. Buckley
et al.

Abstract: Background Soil and phyllosphere (leaves and fruit) microbes play critical roles in the productivity and health of crops. However, microbial community dynamics are currently understudied in orchards, with a limited number incorporating temporal monitoring. We used 16S rRNA gene amplicon sequencing to investigate bacterial community temporal dynamics and community assembly processes on the leaves and fruit, and in the soil of 12 kiwifruit orchards across a cropping season in New Zealand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…It is well-known that ecological drift is attributed to random processes like immigration or emigration of microbial taxa, and pronounced under conditions where microbial diversity is low 58 , 59 . A study of bacterial community temporal dynamics confirmed that stochastic processes were important during the colonization of the phyllosphere 60 . However, in our study, the standard effect size of non-random processes on leaf biofilm compositional dissimilarity (Bray–Curtis) was higher than two when compared between plants, between treatments, and between sampling occasions except for the first day of the experiment (Supplementary Table S2 ).…”
Section: Discussionmentioning
confidence: 87%
“…It is well-known that ecological drift is attributed to random processes like immigration or emigration of microbial taxa, and pronounced under conditions where microbial diversity is low 58 , 59 . A study of bacterial community temporal dynamics confirmed that stochastic processes were important during the colonization of the phyllosphere 60 . However, in our study, the standard effect size of non-random processes on leaf biofilm compositional dissimilarity (Bray–Curtis) was higher than two when compared between plants, between treatments, and between sampling occasions except for the first day of the experiment (Supplementary Table S2 ).…”
Section: Discussionmentioning
confidence: 87%